Factors Contributing to the English National Achievement Test (Nat) Performance - Anub, Cheryl Dalapo (Middle Eastern Journal of Research in Education and Social Sciences, 2020)
Purpose: The main purpose of this study was to determine the factors that contributed to the English National Achievement Test (NAT) Performance of the Top Five High Performing Secondary Schools in the Division of Bohol for school years 2009-2010 and 2010-2011. Approach/Methodology/Design: It utilized descriptive-correlational research design through survey method. Findings: The results of the study revealed that the practices of the teachers on the school factors that affect students’ English NAT performance were having: class size of 31 to 50 students, a student-book ratio of 1:1, monthly supervision of heads, review classes every Saturday and remedial teaching as the need arises. However, there was a significant relationship between all the four teacher factors namely: age, highest educational attainment, length of service and number of relevant seminars; eight of the nine school factors. Teacher’s age, number of relevant seminars attended, conduct of remedial teaching and students’ academic performance are the factors contributing to the students’ English NAT results for school year 2009-2010 while teacher’s number of relevant seminars attended, varying teaching strategies, pairing low performing students with high performing ones and students’ academic performance are the factors contributing to the students’ English NAT results for school year 2010-2011. Practical Implications: The results of this studying should be taken into account in order to improve students’ NAT performance in English. Originality/value: This research concludes that all the factors are interrelated.